Exploring genomic, geographic and virulence interactions among epidemic and non-epidemic St. Louis Encephalitis Virus (Flavivirus) Strains - Diaz, Luis Adrian (2015)
St. Louis encephalitis virus (SLEV) is a re-emerging arbovirus in South America. In 2005, an encephalitis outbreak caused by SLEV was reported in Argentina. The reason for the outbreak remains unknown, but may have been related to virological factors, changes in vectors populations, avian amplifying hosts, and/or environmental conditions. The main goal of this study was to characterize the complete genome of epidemic and non-epidemic SLEV strains from Argentina. Seventeen amino acid changes were detected; ten were non-conservative and located in proteins E, NS1, NS3 and NS5. Phylogenetic analysis showed two major clades based on geography: the North America and northern Central America (NAnCA) clade and the South America and southern Central America (SAsCA) clade. Interestingly, the presence of SAsCA genotype V SLEV strains in the NAnCA clade was reported in California, Florida and Texas, overlapping with known bird migration flyways. This work represents the first step in understanding the molecular mechanisms underlying virulence and biological variation among SLEV strains.